The positive effects of caring for family carers of older adults: a scoping review. (1st August 2020) - Pysklywec, Alex; Plante, Michelle; Auger, Claudine; Mortenson, William B.; Eales, Jacquie; Routhier, François; Demers, Louise
Abstract : The negative effects of caring are well documented; however, positive effects have received less attention. A scoping review of 22 studies published between 2000 and 2018 was conducted regarding the positive effects of family caring for older adults. Our analysis revealed that positive effects are embedded in relationships, summarised in three themes: in relationship with one's self (the carer), for example, personal growth; in relationship with the care recipient, for example, a deepened dyadic relationship; and in relationship with others, for example, new care-related relationships. Seeing the positive effects of caring relationally may shape environmental factors, such as assistive device, social policy or health services development.